2017
DOI: 10.4236/psych.2017.810101
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Immediate and Future Consequences in Accepting and Responding to Anthropogenic Climate Change

Abstract: Decreasing greenhouse gas emissions (climate change mitigation) is one of the most important types of pro-environmental behavior. Greenhouse gases have been repeatedly cited as a leading cause of climate change (CC). However, before engaging in CC mitigation behaviors, individuals must accept the reality of CC. Few studies addressing the influence of individual time perspective on climate change mitigation have been found. No study investigating the relationship between time perspectives and acceptance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…In line with our expectations, we found that biospheric value and concern with future consequences (CFC-F) have both positive effects on adaptation policy support and mitigation intention (for similar results, see Corral-Verdugo et al, 2017;Dietz et al, 2007;Khachatryan et al, 2013;Marshall et al, 2019;Xie et al, 2019). Interestingly, biospheric preference has a stronger effect on mitigation intention than support for adaptation policy.…”
Section: The Role Of Biospheric Motivation and Concern With Future Cosupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our expectations, we found that biospheric value and concern with future consequences (CFC-F) have both positive effects on adaptation policy support and mitigation intention (for similar results, see Corral-Verdugo et al, 2017;Dietz et al, 2007;Khachatryan et al, 2013;Marshall et al, 2019;Xie et al, 2019). Interestingly, biospheric preference has a stronger effect on mitigation intention than support for adaptation policy.…”
Section: The Role Of Biospheric Motivation and Concern With Future Cosupporting
confidence: 89%
“…Previous studies have found that orientation on immediate consequences is negatively associated with environmental concern and motivation (Arnocky et al, 2014) and proenvironmental behavior (see a meta-analysis by Milfont et al, 2012), whereas orientation on the future is positively associated with environmental concern and motivation (Arnocky et al, 2014) and proenvironmental intention and behavior (Bruderer Enzler, 2015;Joireman et al, 2001Joireman et al, , 2004; see also a meta-analysis by Milfont et al, 2012). Essentially, same patterns have been observed regarding climate change mitigation: future orientation is positively associated with support for mitigation policies and individual mitigation behavior (Corral-Verdugo et al, 2017;Dietz et al, 2007;Khachatryan et al, 2013), whereas immediateorientation is negatively associated with mitigation behavior and policy support (e.g., Khachatryan et al, 2013; but see Corral-Verdugo et al, 2017, who failed to find such an effect). No research has focused on the effect of temporal preferences on adaptation attitude and behavior.…”
Section: Temporal Dilemma Preferencesmentioning
confidence: 78%
“…For example, the preference for biofuel over gasoline was inversely related to the consideration of immediate consequences and positively related to the consideration of distant consequences (Khachatryan et al, 2013). Similarly, climate change acceptance and commitment to engage in mitigation actions was influenced by CFC-distant, yet, consideration of immediate consequences produced no effect (Corral-Verdugo et al, 2017). In contrast, Arnocky et al (2014) found that lower levels of CFC-immediate predicted environmental concern and motivation for pro-environmental behavior, but that there were no significant effects by CFC-distant.…”
Section: Consciousness For Sustainable Consumption and The Consideratmentioning
confidence: 99%
“…Furthermore, the relation between CSC and CEC will be positive regarding distant future consequences and negative with immediate future consequences. Prior evidence of a significant effect on behavior from immediate and distant future considerations is contradictory (e.g., Arnocky et al, 2014;Corral-Verdugo et al, 2017). However, sustainable consumption implies that people take into account the relationship between short-term and long-term benefits of their consumption.…”
Section: Consciousness For Sustainable Consumption and The Consideratmentioning
confidence: 99%
“…Furthermore, in a PE, the responsible actions of individuals are triggered by affordances that enable pro-environmental and prosocial behaviors making possible the conservation and integrity of that environment. These enablers of responsible actions include physical urban design that facilitates sustainable actions, information to cope/solve environmental problems, social models of responsible behavior, perceived legitimacy of authorities tasked with addressing important social issues, and government programs guaranteeing access to social justice and equity, ( Corral-Verdugo et al, 2017 ). It is possible to identify enablers of responsible behaviors (i.e., healthy, precautionary) in the framework of COVID-19.…”
Section: Introductionmentioning
confidence: 99%